Investigation of physical, physiological and neuromuscular performance parameters of elite sailing athletes - Ömer, A.; Mehmet, S.; Can, G. Ü.; Ugur, C.; Onur, Y. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background Elite sailing performance depends on the interaction of anthropometric features, strength-power capacities, postural control, and physiological fitness. However, sex-specific neuromuscular and physiological profiles in competitive sailing remain insufficiently characterized. Therefore, this study aimed to examine sex-related differences in the physical, physiological, and neuromuscular attributes of elite sailors using an integrated laboratory-based test battery.